The State of the Vaginal Microbiocenosis, Bacterial Vaginosis and its Treatment Options - Zhumaeva, D. R. (American Journal of Bioscience and Clinical Integrity, 2024)
Bacterial vaginosis (BV) is a common pathological condition occurring in women of reproductive age, which includes a complex of changes in the vaginal biotope, characterized by a decrease in the amount of normal microflora and an increase in the concentration of other microorganisms, especially gram-negative anaerobes such as Prevotella Porphyromonas spp ., Peptostreptococcus spp ., Fusobacterium spp ., Mobiluncus spp.